Avaliação da coagulação sanguínea no choque hemorrágico controlado após reposição volêmica com ringer lactato, sangue total, plasma fresco congelado e glóbulos, em ratos - Gilberto Pedro Rodrigues (2014)
Background: The development of coagulation disorders is frequent in severe trauma and contributes significantly to morbidity and mortality. There is controversy about the best volume replacement in trauma. We aimed to evaluate different blood component ratios and crystalloid in the treatment of hemorrhagic shock. Methods: Male albino rats ( n = 36 ) were randomized into 06 groups: SHAM, NP-R , replacement with ringer lactate (RL), NP-R (1:1), NP-R(1:2), NP-R(1:3) replacement with plasma:red blood cells 1:1, 1:2 e 1:3 respectively and NP-TB replacement with fresh whole blood (FWB). All animals, except the SHAM group, underwent to controlled hypovolemic shock followed by resuscitation with the type of fluids described above analyzed by thromboelastometry (NATEM test of the ROTEM®) before and after shock induction. For evaluation of the following parameters were examined at ROTEM®: CT (clotting time), CFT (clot formation time), angle, MCF (maximum clot firmness) and Ly60 (lysis 60). Analysis of variance was done using Turkey post test for comparisons between groups. Results: In the process involving the initiation of clot (CT) no differences between groups were observed. Regarding the kinetics of clot (CFT and ), the NP-R and NP-R (1:3) groups were significantly worse when compared to the other groups. Regarding the clot strength (MCF) NP-R group was significantly worse when compared to SHAM, Baseline, NP-R (1:1), NP-R (1:2) and NP-TB. In addition the NP- R (1:3) was significantly worse as compared to SHAM, Baseline and NP-TB. Values for Ly60 did not vary among groups. Conclusions: The fluid resuscitation with whole blood or with plasma:red blood cells ratios of 1:1 and 1:2 are the best options to treat controlled hemorrhagic shock in rats as less clotting alterations and better hemodynamic responses are achieved when compared to RL or to other PFC:FFP ratios.